Risk transfer and stakeholder relationships in Public Private Partnerships. Issue 1 (April 2017) - Burke, Richard; Demirag, Istemi
Highlights: Using stakeholder theory, the paper evaluates stakeholder relationships in PPPs. Collaborative relationships are evident between the public sector bodies. Procuring Authority adopts a proactive approach towards managing the SPV. Procuring Authority appears to be accommodating towards the SPV with penalties. Taxpayers' needs could be accommodated more in the risk allocation process. Abstract: Drawing on stakeholder theory, this study seeks to gain an insight into the stakeholder management strategies used by the Procuring Authority in Irish road Public Private Partnerships to manage its complex stakeholder relationships. Based on interviews with 38 key stakeholders the findings of this study indicate that the allocation, transfer and management of risk impact on the quality of stakeholder relationships. A proactive and somewhat accommodating approach is used by the Procuring Authority in its relationship with the Special Purpose Vehicle, while there is some evidence that collaborative relationships exist between the public sector bodies responsible for allocating risk.